Evaluating risk factors for acute graft versus host disease in pediatric hematopoietic stem cell transplant patients receiving tacrolimus. Issue 4 (8th April 2021) - Phan, Michael; Chavan, Rishikesh; Beuttler, Richard; Benipayo, Nicole; Magedman, Grace; Buchbinder, David; Tomaszewski, Daniel; Yang, Sun
Abstract: To identify the clinical and pharmacological risk factors associated with tacrolimus pharmacodynamics for acute graft‐versus‐host disease (aGVHD) in pediatric patients receiving allogeneic hematopoietic stem cell transplantation (HSCT) from a matched related donor. A retrospective cohort single center chart review study was conducted with pediatric patients who received tacrolimus prophylaxis after allogeneic HSCT between January 1, 2017, and December 31, 2019. Potential risk factors were tested separately between aGVHD and non‐aGVHD cohorts and were further analyzed in a logistic regression model with backward elimination and a partial least squares discriminant analysis. Thirty‐three patient cases were included in our study and 52% (17/33) developed aGVHD while on tacrolimus prophylaxis. When tested independently, donor age and sibling versus parent donor/recipient relation were shown to be statistically significant between aGVHD and non‐aGVHD patients ( p  < 0.005). Pharmacological factors associated with tacrolimus treatment failed to demonstrate a significant impact on patient's risk of aGVHD. Using a best fit logistic regression model that tested all the variables together, donor age was the only significant variable predicting patient's risk of aGVHD ( p  < 0.01). Donor relationship and donor age were unable to be evaluated separately and are therefore confounding variables. Among pediatric patients receiving allogeneic HSCT, aGVHD risk is significantly decreased by either sibling donor and/or younger donors. Although no conclusions were drawn on the effect of tacrolimus therapy ( p  = 0.08), results warrant additional research with a larger sample size to evaluate the accuracy of monitoring tacrolimus serum trough levels.